Application of Decision Tree Method in ECG Signal Classification For Heart Disorder Detection - Banjarnahor, Jepri; Sinaga, Friska; Sitorus, Dedi Setiadi; Sitanggang, Wahyu Adventus Andreas; Turnip, Mardi (Politeknik Ganesha Medan, 2024)
Cardiovascular Disease (CVD) is a group of diseases that affect the heart and blood vessels, and it is the leading cause of death globally. In Indonesia, Coronary Heart Disease (CHD) is one of the most prevalent CVDs. However, due to the high cost of drugs, lengthy treatment duration, and various supporting examinations required, treating CHD can be very expensive. An obstacle to treating heart disease in Indonesia is the insufficient number of cardiologists and experts experienced in interventional cardiology. Along with technological developments, the computer science community is encouraged to contribute to the medical field. For instance, using an electrocardiogram (ECG) can help prevent and minimize problems arising from heart disease. An Electrocardiogram (ECG) is a medical test that measures and records the heart’s electrical activity using a machine that detects electrical impulses. The use of Artificial Intelligence (AI) in ECG is rapidly increasing and has shown to have great potential in improving the diagnosis and treatment of cardiac patients. AI has become a valuable tool in helping doctors diagnose, predict risk, and manage heart disease with greater accuracy, speed, and precision. One of the machine learning methods used in this research is the decision tree method, which is often employed to make decisions. The decision tree method exhibited promising results, with an accuracy rate of 99% in identifying heart defects at an early stage. This method has significant potential to assist doctors in diagnosing heart defects at an early stage with high accuracy.